(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
Looking for sources of changes in the religiosity of modern societies, attention is paid primarily to global modernization processes. The impact of social microstructures on specific behavior and attitudes of people is often underestimated. In particular, this applies to the family, which impact on social practices undertaken by people, lifestyle preferences or accepted values cannot be overestimated. Therefore, it is worth analyzing how the great family transformations, namely those related to pluralization, deinstitutionalization, and individualization, have influenced the religious attitudes and behavior of its members.